READING COMPREHENSION DIFFICULTIES IN INDONESIAN EFL STUDENTS - Agustina Ramadhianti; Sugianti Somba (Journal of English Language Teaching and Literature (JELTL), 2023)
Getting knowledge by reading is one of the prominent ways, and reading comprehension is a skill to help students in learning process. In fact, there are many EFL students have some difficulties in reading comprehension. The objective of this study is to analyze the students’ difficulties in reading comprehension skills. Descriptive qualitative method is used in this study, and by using purposive sampling, 98 students of Basic Reading Class at English Education Program in University of Indraprasta PGRI were engaged. The data collected by administering the questionnaires, then it was analyzed to find out what kind of the difficulties faced by EFL students in reading comprehension. The questionnaires were administered in collecting the data, and it was analyzed descriptively to know what kind of reading comprehension difficulties faced by EFL students. According to the results, the most reading difficulty faced by the students are distinguishing between main ideas and supporting details, getting main idea between paragraphs, the topic of the texts from other culture, relating topic and background knowledge, understanding vocabulary and inferring the text. Based on these findings, some reading strategies should be applied to figure out these barriers in reading comprehension skills.